1989
DOI: 10.1002/bjs.1800760910
|View full text |Cite
|
Sign up to set email alerts
|

Computer analysis in making preoperative decisions: A rational approach to lymph node dissection in gastric cancer patients

Abstract: In Japan, R2 lymph node dissection is standard practice for all curatively resected gastric cancer patients. From 1969 to 1984, data were collected prospectively to evaluate this procedure and to provide information for a more rational approach to node dissection for each individual case. A total of 3843 cases was included in this study and an evaluation was made of the prognostic variables and lymph node involvement at various locations. Using a computer program, it is possible to compile a group of treated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
5

Year Published

1992
1992
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 8 publications
2
57
0
5
Order By: Relevance
“…Although various models have been proposed to predict lymph node metastasis, the clinical utility of these models is limited. For example, the Maruyama computer model based on several clinical variables (age, sex, tumor type, depth of invasion, location, diameter of the primary tumor and histological type) was initially proposed by Kampschoer in 1989. 24 Subsequent studies showed that although the sensitivity for lymph-node detection was high (97-100%), the specificity was very low (20%).…”
Section: Discussionmentioning
confidence: 99%
“…Although various models have been proposed to predict lymph node metastasis, the clinical utility of these models is limited. For example, the Maruyama computer model based on several clinical variables (age, sex, tumor type, depth of invasion, location, diameter of the primary tumor and histological type) was initially proposed by Kampschoer in 1989. 24 Subsequent studies showed that although the sensitivity for lymph-node detection was high (97-100%), the specificity was very low (20%).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative means of guiding node dissection in a particular case of gastric cancer was pioneered by Kampschoer, Maruyama, and colleagues in 1989 [1]. A meticulously maintained database of 3843 cases from the National Cancer Center, Tokyo, was computerized and, through use of a simple search routine, cases could be matched on the basis of seven characteristics identifiable pre-operatively (age, sex, Borrmann morphologic type, presumed depth of primary tumor, gastric tumor location, maximum tumor diameter, and histologic node stations that should have been dissected) of 51% for patients who should have undergone a D-2 dissection [6].…”
Section: Background: the Maruyama Programmentioning
confidence: 99%
“…To overcome this problem, the Maruyama computer model was developed, and it was first described in the English-language literature in 1989 [7]. The MCP calculates the probability (%) of lymph-node metastases for the different lymph-node positions 1-16, according to the JCGC.…”
Section: Discussionmentioning
confidence: 99%
“…Successful estimation of lymph node involvement may help to define those patients who would and those who would not benefit from an extended lymph node dissection in association with gastrectomy. For this purpose, a computer program was developed by Maruyama and his colleagues [7] to estimate the incidence of lymph node metastases, the expected prognosis, and the proportion of curable cases at surgery, based on the most significant preoperative prognostic factors. This program was later improved as the Windows-based program WinEstimate v. 2.5, using a database of 4302 primary gastric cancer patients treated at the National Cancer Center Hospital in Tokyo between 1968 and 1989 [8].…”
Section: Introductionmentioning
confidence: 99%